Education Pollemic During Covid-19 Pandemic: Creating Participatory Learning During Pandemic - Toji, Maria Ornista; Yufrinalis, Marianus (Proceeding International Conference on Religion, Science and Education, 2022)
The Covid-19 pandemic has brought major changes in the global order of human life. In the world of education in Indonesia, the impact caused by this pandemic has brought the Indonesian people to the introduction of a new civilization or era related to mastery of communication and information technology through the application of online learning. However, the readiness of the community in recognizing the use of new technology and applying it in online learning has become a problem in itself during the pandemic period until now. This research uses descriptive qualitative methods and emphasizes data collection through interviews, observation and documentation study. The results reveal the main factors causing stagnation in online learning, namely the low level of community participation in the use of the latest technology as a result of their unpreparedness to accept sudden changes, lack of digital literacy, lack of income for economic needs, and the mentality of students who do not want to study for a long time of pandemic period. Based on these findings, it can be concluded that the unstable economic conditions of society lead to unpreparedness in accepting online learning models through modern learning applications on the internet, including the mentality of people who do not want to accept changes quickly and accelerate in the changes themselves.